Improved Manufacturing Quality and Bonding of Laser Machined Microfluidic Systems. (2015) - Mohammed, Mazher Iqbal; Quayle, Kim; Alexander, Richard; Doeven, Egan; Nai, Ryan; Haswell, Stephen J.; Kouzani, Abbas Z.; Gibson, Ian
Abstract: Laser micro-machining offers a versatile tool for the rapid manufacturing of polymeric microfluidics systems, with a typical turn-around-time in the order of minutes. However, the chaotic nature of the thermal evaporative ablation process can yield a significant number of defects in the surface of the manufactured microchannels, in the form of residual condensed material. In this work we have investigated the use of solvent evaporation by which to not only laminate bond the laser machined structures but to remove a significant number of the defect formed by the condensation of residual polymer. Results are presented of the surface profiling of the bonded channel structures and demonstrations of the bonding of the microchips to produce autonomous capillary microchannels.